Assessment of Academic Achievements of Special Children - Khizar Hayat; Muhammad Hafeez (Universitas Pendidikan Ganesha, 2021)
Life skills are the social and psychological abilities that are very helpful in the learning process and to develop a healthy and sound society. These skills play a key role in academic achievement of students. The better academic achievements and life skills provide a way to the better academic achievements. Life skills development also played an important role for the development of a society and nation. So, knowing the importance of life skills a research study was conducted. This study aims to investigate the life skills of male and female mentally retarted students (ii) to assess the life skills of female and male mentally retarded students as perceived by their teachers (iii) to analyze the academic achievements of the mentally retarded students (iv) to investigate the impact of the life skills of mentally retarded students on their academic achievement. The total 20 students of 10th grade were selected for the current study. The researcher used questionnaire for data collection. The questionnaires were distributed among the concerned teachers. The academic achievements of 10th grade students with mental retardation were analysed by using descriptive statistics and percentage formula. The results of the study showed that students with mental retardation achieved low academic scores. Out of 20 students, 4 students got 33% marks, 7 students got 33-40% marks, 5 students got 41-50% marks, 4 students got 51-60% marks and no students got more than 60% marks. This low academic achievements of students with mental retardation indicated that children with mental retardation needs special care and extra efforts to achieve better academic achievements. So, it is suggested that special care children must be cared with special attention.